Comparing the Effectiveness of Cognitive Empowerment Based on Cognitive Games and Executive Function–Based Parenting on Working Memory in Children with Executive Function Deficits - Abbaszadeh , Fatemeh; Salim Bahrami , Seyedeh Hamideh; Emadian, Seyedeh Olia (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to compare the effectiveness of cognitive empowerment based on cognitive games and executive function–based parenting training on improving working memory among children with executive function deficits. Methods and Materials: This research employed a quasi-experimental design with a pretest–posttest control group structure. The statistical population consisted of all 5- and 6-year-old children with executive function deficits in the city of Qaemshahr. A total of 60 participants were selected through purposive sampling based on inclusion and exclusion criteria and were randomly assigned to three groups (n = 20 per group): a cognitive game–based cognitive empowerment group, an executive function–based parenting group, and a control group. The first experimental group participated in 11 sessions of 90-minute cognitive game activities designed to enhance working memory, while the second experimental group received 11 sessions of 90-minute executive function–based parenting training. The control group received no intervention during the study period. Working memory was assessed using a standardized Working Memory Test. Data were analyzed using Multivariate Analysis of Covariance (MANCOVA). Findings: The results of the multivariate analysis of covariance indicated significant differences among the three groups in posttest working memory scores after controlling for pretest performance (p < .05). Both cognitive empowerment based on cognitive games and executive function–based parenting interventions significantly improved working memory in children with executive function deficits compared with the control group (p < .05). Furthermore, post hoc comparisons demonstrated that the cognitive game–based cognitive empowerment intervention produced significantly greater improvements in working memory than the executive function–based parenting program (p < .05), indicating superior effectiveness in enhancing cognitive performance. Conclusion: The findings suggest that both cognitive game–based cognitive empowerment and executive function–based parenting interventions are effective approaches for improving working memory in children with executive function deficits. However, cognitive empowerment through structured cognitive games appears to yield stronger outcomes. These results highlight the value of incorporating cognitive training programs and parent-focused executive function interventions into educational and therapeutic settings to support cognitive development in young children experiencing executive function challenges.